Prebiotics Application to Increase Growth and Feed Efficiency on Catfish (Clarias sp. - Achmad Noerkhaerin Putra (Jurnal Perikanan dan Kelautan, 2016)
This study aimed to evaluate the effect of prebiotics supplementions oncarbohydrate based diets on growth and feed efficiency in catfish. This experimentconsisted of three treatments with three replications. The treatments were 0%prebiotic (A); 1% prebiotic (B) and 2% prebiotic C. prebiotic used was extractedfrom sweet potato (varieties: sukuh). Tilapia with an average body weight of50±0.05 g were stocked at a density of 15 fish/ponds and were maintained for 30days.The results showed that application prebiotic in catfish fed can promotebetter growthand feed eficiency compared to control. Application prebiotic 2%(C) showed best result on growth (SGR) and feed efficiency which wassignificantly different (P<0.05) from the other treatments.